ANALISIS YURIDIS PERATURAN TERKAIT ARSITEKTUR BANGUNAN BERCIRIKHAS DAERAH ISTIMEWA YOGYAKARTA - Bagus Anwar Hidayatulloh (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT This study examines the juridical analysis of regulations related to the architecture of the Yogyakarta Special Region. Whereas the regulation of architectural buildings with cultural characteristics has been regulated in several regional regulations, including regional regulations, governor regulations, and mayor regulations. This research is a library research (library research) and combined with field research that is descriptive analytical. So that bringing up the form of approach is a normative approach. The results of this study are regulations related to architectural regulations that characterize the Special Region of Yogyakarta experiencing strengthening in terms of its jurisdiction, especially with the birth of Regional Regulation with the birth of Yogyakarta Special Region Regulation Number 1 Year 2017 Concerning Distinctive Characteristics of Yogyakarta Special Region. In terms of the substance of the existing regulations will strengthen the legal umbrella of Yogyakarta's architectural pluralism, strengthen the area of ​​cultural heritage and the area of ​​cultural heritage. Then in terms of the laws and regulations, it is necessary to harmonize regulations related to building architecture with special character of Yogyakarta Special Region so that the implementation of architectural buildings unique to the Special Region of Yogyakarta can be maintained and optimally maintained.